PERCEPTION AND ATTITUDE OF HEALTH-CARE PERSONNEL REGARDING THE CONCEPT OF INTEGRATION IN NURSING - Patil, Neelam D; Mohite, Vaishali R; Gholap, Manisha C; Chendake, Mahesh (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: To assess the perception of health-care personnel regarding the concept of integration in nursing, to assess the attitude of health-care personnel toward the concept of integration in nursing, and to determine the association of perception and attitude toward the concept of integration in nursing with selected socio-demographic variables. Methods: Research approach adopted was descriptive survey approach. Population were 159 health-care personnel's working at various hospitals and institutions in Maharashtra. Purposive sampling technique was used. Data were collected using structured rating scale, which consisted of 3 sections. Section 1 comprising demographic data, Sections 2 and 3 consisted 10 questions to assess the perception and attitude of health-care personnel. Tool was developed pretesting and reliability of the rating scale was done. Results: Findings of the study showed that majority 118 (74.21%) of respondents had low perception, 41 (25.78%) had medium perception, and none of respondents had high perception regarding the concept of integration. Classification of respondents based on the levels of attitude, the 79 (49.68%) had unfavorable attitude, 75 (47.16%) had moderately favorable attitude, and 5 (3.14%) had favorable attitude. Conclusions: As the result shows that there is medium to low level of perception between the health-care personnel regarding the concept of integration and the attitude is also unfavorable, there is need to find out the barriers of integration in nursing profession. Keywords: Perception, Attitude, Integration, Health-care personnel.